SERVING MAP WITH OGC STANDARDS VIA NETWORK - Birgoren, M.; Gumusay, U. (COPERNICUS GESELLSCHAFT MBH, 2010)
Using geographic information economically is important as much as getting geographic information. In our country geographic information is reproduced when not sharing it between each organizations (General Command of Mapping, TKGM, Bank of Province, Municipalities etc). Reproducing data is effect country economy negatively. With sharing geographic information independent from hardware and software via computer network, reproduce same information is being prevented and costs are reduces. This independence is obtained with developing and implementing international standard. The Open Geospatial Consortium (OGC) is established for this aim and improves standards about sharing geographic information via network. The aim of research is to expose what kind of benefits gain from sharing, using and presenting geographic information at international standards; to offer suggestions with comparing some software which make map service at international standards. In this document Web Map Service (WMS)'s structure and which OGC standards will be applied when serving map via network are described. Besides, Geoserver, MapServer and ArcGIS Server software are tested which will serve map. These software use Hypertext Transfer Protocol (HTTP) to communicate between service and client. Response time of service is compared between each other with using raster data.
Keywords: OGC; Map Service; Standard; Geoserver; Mapserver; ArcGIS Server; Physical Geography; Remote Sensing; Imaging Science & Photographic Technology